Karakteristik dan Pengaruh Luas Lahan terhadap Produksi Kopi Sistim Organik di Kawasan Hutan - Suminartika, Eti; Saidah, Zumi; Deliana, Yosini (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Organic coffee farming has a higher selling price than non-organic coffee, organic coffee farm business is a source of employment and income for farmers. Coffee planting in forest areas is different from coffee planting in farmers' gardens, because coffee planters in the forest are planted in between forest plants, the number of coffee plants planted in the forest becomes smaller in number (not optimal). The purpose of the research is to examine the characteristics of farmers and their businesses and to analyze the effect of the land area on organic coffee production in the Girisenang forest farmer group (Kelompok tani hutan/KTH).  The research method used is a case study, the data used consists of primary and secondary data, primary data obtained from sample farmers by census.  The analysis used is descriptive analysis and econometric analysis, namely linear regression equations.  The results showed: (1) Organic coffee farmers in (KTH) Girisenang are mainly farmers, with low education, productive age.  The average area of forest land cultivated is 1 hectare, the average number of plants is 1272 trees, fertilizing oranically, maintaining their gardens according to recommendations, harvesting coffee in the form of cerry, and (2) Land area has no significant effect on production, because the number of coffee plants in the forest land farming area are not optimal.